2021
DOI: 10.3390/healthcare9020210
|View full text |Cite
|
Sign up to set email alerts
|

Postural Sway in Older Patients with Sagittal Imbalance and Young Adults during Local Vibratory Proprioceptive Stimulation

Abstract: This study aimed to assess differences in somatosensory control strategies between older patients with sagittal imbalance and young adults during postural tasks. The center of pressure displacement in 27 older patients with sagittal imbalance and 27 young adults was determined upon standing blindfolded on a balance board. Vibratory stimulation at 56 to 100 Hz was applied bilaterally to the gastrocnemius and soleus muscles (GS) and lumbar multifidus to evaluate the contributions of proprioceptive signals to pos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 49 publications
1
4
0
Order By: Relevance
“…These results are consistent with those of a previous study that showed a greater postural response to the vibratory stimulation of the lower legs when vibration was applied to the lower legs. In a previous study, in which similar mechanical vibration stimulation was used in young healthy individuals, the amount of response was greater when vibratory stimulation was applied to the lower legs than to the lower back, and this trend was also observed in the present study [28]. In both the lower legs and lower back, the standard deviation of the indicator at ES 3 was large.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…These results are consistent with those of a previous study that showed a greater postural response to the vibratory stimulation of the lower legs when vibration was applied to the lower legs. In a previous study, in which similar mechanical vibration stimulation was used in young healthy individuals, the amount of response was greater when vibratory stimulation was applied to the lower legs than to the lower back, and this trend was also observed in the present study [28]. In both the lower legs and lower back, the standard deviation of the indicator at ES 3 was large.…”
Section: Discussionsupporting
confidence: 88%
“…The percentage of functional decline for both the lower legs or the lower back in ES 3 was smaller than that in ES 1 and ES 2 . Previous studies [ 26 , 27 , 28 ] have not reported differences in the susceptibility of muscle spindles or the Vater–Pacini corpuscle to hypofunction in healthy individuals. The results of this study suggest that some healthy participants may have a Vater–Pacini corpuscle with a decline in proprioceptive function.…”
Section: Discussionmentioning
confidence: 94%
“…It is known that patients with ASD have impaired postural control ( 4 - 6 ). Although some pre- and post-surgery trials have determined differences in some measures of postural control after spinal surgery for ASD ( 22 ), most studies fail to show significant differences following surgical re-alignment ( 23 ).…”
Section: Discussionmentioning
confidence: 99%
“…Patients with ASD show impairment in postural control; the maintenance of standing balance. Increased center of pressure (COP) amplitudes are indicative of unsteadiness ( 4 - 6 ). Ito et al , for example, found patients having a SVA >40 mm showed greater root mean square (RMS) displacement in the eyes closed (EC) condition vs. a young and healthy control group ( 4 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation